Borders as penal transplants: Control of territory, mobility and illegality in West Africa - Stambøl, Eva Magdalena (Theoretical criminology, 2021)
This article explores an increasingly significant trend in crime and mobility control that has received scant criminological attention: border externalization, specifically scrutinizing land border security-building by international actors in West Africa. Going beyond the usual focus on migration in border studies, it develops a criminologically grounded theorization of the border as a political technology of crime control and its relationship to the state. This is done by arguing that borders, theorized as ‘penal transplants’ embodying specific (western) visions of state, political power, social control/order and territoriality, are transformed and often distorted when performed in ‘heterarchical’ contexts in the global South. Further, empirically based concepts from ‘the periphery’ are suggested to enrich border criminology, broadening its geographical scope and spatial awareness.